Aktivitas Antioksidan Kopibiji Rambutannon Kafein Dengan Variasi Perbandingan Komposisi Beras Hitam Yang Berbeda - Kadapi, Muamar, Triastuti Rahayu, S.Si, M.Si (2015)
Coffee is a beverage dark black with a special aromatic,usually brewed using hot water and basically have a bitter taste. Products can be made from rambutan seed with the addition of black rice that produce coffee non caffeine. Rambutan seed contains carbohydrates, fats, proteins, fibers which can meet the nutritional needs of the body and also contains polyphenols high enough as an antioxidant and antibacterial activity. Black rice contains carbohydrates, of protein, fat, fiber and has a pericarp, aleurone and endosperm red-blue-purple thick, the color indicates the presence of anthocyanin content. The purpose of this study was to determine the antioxidant activity as well as organoleptic quality coffee non caffein. This research method with DPPH to activity antioxidant and a completely randomized design (CRD) with one factor, namely: rambutan seed composition ratio with black rice. Results showed the highest antioxidant activity content on R3 treatment is 29.29%, R1 treatment has antioxidant activity of 23.29% and the lowest antioxidant activity in R2 treatment is 19.97%. Product decaffeinated coffee is the most dominant black color, taste fresh, distinctive aroma of coffee and acceptance of the most dominant panelists liked R3 treatment.